2022
DOI: 10.3233/wor-210922
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the mediation role of employees’ well-being in the relationship between psychosocial factors and musculoskeletal pain during the COVID-19 pandemic

Abstract: BACKGROUND: The COVID-19 pandemic has increased some psychosocial risks which may aggravate the development of musculoskeletal disorders (MSDs) and reduced psychological well-being, two leading global occupational health problems. OBJECTIVE: This study aims to investigate whether an employee’s psychological well-being mediates the relationship between the psychosocial factors (job strain, work-life balance, and job security) and the prevalence of musculoskeletal pain in the Indonesian general working populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 61 publications
(137 reference statements)
1
8
0
Order By: Relevance
“…The present study did not consider other factors, such as psychosocial, psychological, and organizational, that may have influenced the perception of pain/discomfort experienced by the teleworkers. These nonphysical risk factors are known to play a role in the development of musculoskeletal disorders (e.g., Bongers et al, 1993 ; Carayon et al, 1999 ; Graveling et al, 2021 ), and some factors may be more relevant than others, as reported by Sutarto et al (2022) . However, their analysis and complex relationship with physical factors and subjective outcomes ( Graveling et al, 2021 ; Sutarto et al, 2022 ), which are mediated by multiple mechanisms (biomechanical, neurological, physiological, and neuroendocrine), was beyond the scope of this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study did not consider other factors, such as psychosocial, psychological, and organizational, that may have influenced the perception of pain/discomfort experienced by the teleworkers. These nonphysical risk factors are known to play a role in the development of musculoskeletal disorders (e.g., Bongers et al, 1993 ; Carayon et al, 1999 ; Graveling et al, 2021 ), and some factors may be more relevant than others, as reported by Sutarto et al (2022) . However, their analysis and complex relationship with physical factors and subjective outcomes ( Graveling et al, 2021 ; Sutarto et al, 2022 ), which are mediated by multiple mechanisms (biomechanical, neurological, physiological, and neuroendocrine), was beyond the scope of this study.…”
Section: Discussionmentioning
confidence: 99%
“…These nonphysical risk factors are known to play a role in the development of musculoskeletal disorders (e.g., Bongers et al, 1993 ; Carayon et al, 1999 ; Graveling et al, 2021 ), and some factors may be more relevant than others, as reported by Sutarto et al (2022) . However, their analysis and complex relationship with physical factors and subjective outcomes ( Graveling et al, 2021 ; Sutarto et al, 2022 ), which are mediated by multiple mechanisms (biomechanical, neurological, physiological, and neuroendocrine), was beyond the scope of this study. Such endeavor would have required additional questionnaires and thus reduced the number and quality of responses.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with recent literature that highlights the potential of HRM to address unemployment issues, our focus in this article is to highlight the short-and long-term consequences of job loss resulting from COVID-19 for financial strain and the negative impacts of financial strain on both short-and long-term subjective well-being. What clearly emerges from the literature is that COVID-19 has had a major impact on employee psychological health and well-being (Schwab et al 2022;Sutarto, Wijayanto and Afiah 2022). According to the APAs COVID-19 Practitioner Impact Survey (2022), psychological well-being is one of the major outcomes of the pandemic leading to early retirement, the great resignation, decreased mental well-being, reduced ability to engage with the workforce post-pandemic and a significant mental health crisis.…”
Section: Introductionmentioning
confidence: 99%
“…What clearly emerges from the literature is that COVID‐19 has had a major impact on employee psychological health and well‐being (Schwab et al. 2022; Sutarto, Wijayanto and Afiah 2022). According to the APAs COVID‐19 Practitioner Impact Survey (2022), psychological well‐being is one of the major outcomes of the pandemic leading to early retirement, the great resignation, decreased mental well‐being, reduced ability to engage with the workforce post‐pandemic and a significant mental health crisis.…”
Section: Introductionmentioning
confidence: 99%
“…Because of COVID-19, several firms have offered their employees to perform their duties from home during the lockdown period (Sutarto, Wijayanto, & Afiah, 2021), and Bangladeshi enterprises do not differ (Ahmed & Islam, 2022). Work-from-home and remote working were identified as significant actors of WLB under the "new normal" condition and were also recognized as important for women's work-life balance (Uddin, 2021).…”
Section: Introductionmentioning
confidence: 99%